Treatment of Cerebral Ischemia Through NMDA Receptors: Metabotropic Signaling and Future Directions - Li, Yuanyuan; Cheng, Xiaokun; Liu, Xinying; Wang, Le; Ha, Jing; Gao, Zibin; He, Xiaoliang; Wu, Zhuo; Chen, Aibing; Jewell, Linda L.; Sun, Yongjun (Frontiers in Pharmacology, 2022)
Excessive activation of N-methyl-d-aspartic acid (NMDA) receptors after cerebral ischemia is a key cause of ischemic injury. For a long time, it was generally accepted that calcium influx is a necessary condition for ischemic injury mediated by NMDA receptors. However, recent studies have shown that NMDA receptor signaling, independent of ion flow, plays an important role in the regulation of ischemic brain injury. The purpose of this review is to better understand the roles of metabotropic NMDA receptor signaling in cerebral ischemia and to discuss the research and development directions of NMDA receptor antagonists against cerebral ischemia. This mini review provides a discussion on how metabotropic transduction is mediated by the NMDA receptor, related signaling molecules, and roles of metabotropic NMDA receptor signaling in cerebral ischemia. In view of the important roles of metabotropic signaling in cerebral ischemia, NMDA receptor antagonists, such as GluN2B-selective antagonists, which can effectively block both pro-death metabotropic and pro-death ionotropic signaling, may have better application prospects.